Does fiscal consolidation hurt economic growth? Empirical evidence from Spanish regions - Santiago Lago Pe\~nas; Alberto Vaquero-Garcia; Patricio Sanchez-Fernandez; Beatriz Lopez-Bermudez (Kiel Institute for the World Economy (IfW), 2019)
This article provides empirical evidence on the effect of fiscal consolidation in decentralized countries. The focus on Spain is justified for three reasons. First, it is one of the OECD countries that has been the most affected by the Great Recession in terms of both GDP and public deficit. Second, it is one of the most decentralized countries in the world. Third, the compliance with fiscal consolidation targets has been very diverse across regions. Using both time series econometrics and the synthetic control method approach (SCM), the authors show that compliance with fiscal targets at the regional level has not involved lower GDP growth rates in the short run.
https://doi.org/10.7910/DVN/KFQJPN
Keywords: H74; R11; H62; 330; fiscal consolidation; regional economic growth; great recession